Microplastics and Nanoplastics in the Human Diet: Sources of Exposure, Bioavailability, Toxicokinetics, and Systemic Health Effects - Łukasz Kogut; Czesław Puchalski; Julia Jastrzębska; Grzegorz Zaguła (Molecules, 2026)
Background/Objectives: Microplastics (MPs) and nanoplastics (NPs) have emerged as ubiquitous environmental contaminants resulting from the extensive production, use, and degradation of plastic materials. Human exposure occurs primarily through contaminated food and drinking water, with inhalation representing an additional important route. Growing concern has focused on the ability of these particles, particularly NPs, to cross biological barriers, enter the systemic circulation, and reach human tissues. The aim of this review was to summarize current evidence on dietary exposure to MPs and NPs, their gastrointestinal bioavailability and toxicokinetics, and their potential systemic health effects, with particular emphasis on organ-specific responses, underlying biological mechanisms, and the strength and limitations of the available evidence. Methods: A comprehensive narrative review of the scientific literature published between 2000 and 2026 was conducted using PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar. Original research articles and review papers addressing dietary exposure, occurrence in food and drinking water, migration from food-contact materials, gastrointestinal absorption, translocation, biodistribution, bioaccumulation, elimination, molecular mechanisms, and potential organ-specific or systemic health effects were included. Publications without full-text availability, conference proceedings, editorials, commentaries, duplicate publications, and studies without relevance to human exposure or health were excluded. Results: Food, drinking water, beverages, and food-contact materials represent important sources of human exposure to MPs and NPs. Following ingestion, most larger particles are eliminated through the gastrointestinal tract, whereas smaller MPs and particularly NPs may cross biological barriers and potentially reach the systemic circulation and distant tissues. Experimental studies consistently identify interconnected biological responses involving oxidative stress, inflammation, mitochondrial dysfunction, barrier impairment, immune dysregulation, genotoxicity, apoptosis, and endocrine disruption. These mechanisms have been associated with alterations in the gastrointestinal, respiratory, cardiovascular, nervous, urinary, reproductive, endocrine, and skeletal systems and with biological processes relevant to carcinogenesis. However, most mechanistic evidence derives from in vitro and animal models, whereas human evidence remains limited and predominantly observational. Consequently, the extent to which these experimental findings translate into clinically significant effects in humans remains uncertain. Conclusions: Current evidence supports the biological plausibility of systemic effects associated with MNP exposure but is insufficient to establish causal relationships between chronic dietary exposure and specific human diseases. The detection of MNPs in human tissues and reported associations with pathological conditions should therefore be interpreted cautiously. Standardized analytical methods, improved characterization of realistic human exposure, and well-designed longitudinal epidemiological studies integrating quantitative exposure assessment with validated clinical outcomes are required to clarify dose–response relationships, long-term health effects, and the clinical significance of MNP exposure.